2015
DOI: 10.1039/c4nr07589g
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-dependent optical behaviors of colloidal CdSe nanoplatelets

Abstract: Two-dimensional (2D) colloidal anisotropic CdSe nanoplatelets (NPLs) have attracted a great deal of attraction within recent years. Their strong thickness-dependent absorption and emission spectra exhibit significant differences from those of other shaped CdSe nanocrystals (NCs) due to a unique atomically flat morphology. Based on their dielectric confinement effect and the large confinement energy, the 2D CdSe NPLs exhibit the best characteristics of optical and electronic properties as compared to the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Nanocrystals (NCs) respond specifically to pressure with respect to phase progression, coherent crystal domain size, particle agglomeration, and morphology, accompanied by physical and chemical property modification. For example, high pressure can induce distinct textural coalescence of metallic Au/Ag NCs along with tuning the corresponding plasmonic resonance; (meta)stable phases in conventional semiconductors including CdSe and PbS/Pt;[15a,16] and alternation in the carrier dynamics in CdTe NCs and CsPbBr 3 perovskite nanocube superlattices …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocrystals (NCs) respond specifically to pressure with respect to phase progression, coherent crystal domain size, particle agglomeration, and morphology, accompanied by physical and chemical property modification. For example, high pressure can induce distinct textural coalescence of metallic Au/Ag NCs along with tuning the corresponding plasmonic resonance; (meta)stable phases in conventional semiconductors including CdSe and PbS/Pt;[15a,16] and alternation in the carrier dynamics in CdTe NCs and CsPbBr 3 perovskite nanocube superlattices …”
mentioning
confidence: 99%
“…The dissociation of the NCs is driven by PbBr 6 octahedral tilting and MA cation reorientation accompanying transformation to the orthorhombic polymorph. This growth mechanism differs from that in metallic/organic semiconductor nanoparticles (Au, Ag, CdSe, and PbS)[14a,15] and CsPbBr 3 perovskite quantum dots (QDs), i.e., pressure‐driven large single‐crystal formation from direct attachment and sintering of those nanoparticles. Although it is difficult to realize such high pressure in real applications, similar effects can be achieved by other means, such as chemical substitution, local strain, and tension.…”
mentioning
confidence: 99%
“…The distance inhibits the Förster resonance energy transfer (FRET) within QDs, thus reducing the nonradiative recombination caused by the FRET [ 19 , 20 ]. Furthermore, the elevated pressure in the QD-ZnS NIAM helps to transfer the assembly from a metastable structure to a stable structure that increases the overall stability, according to the literature [ 21 ]. In addition, the PL enhancement at the beginning can be explained by the reduced nonradiative recombination rates in QDs through thermal annealing according to reported studies [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…www.angewandte.de surveyed, and the PL response of each geometry to different pressure states can be seen in Figure 10. [114][115][116][117][118][119][120][121] ThePLo f0D NCs subjected to highly anisotropic shock pressures were shown to initially blue-shift and eventually red-shift to their original position. [127][128][129] Theu nique behavior observed in these studies was ascribed to the complex interactions that dynamic shockwaves have on the loading matrixes.…”
Section: Discussionmentioning
confidence: 97%
“…Thep ressure dependence of the PL of 2D CdSe nanoplatelets (NPs) was also investigated. [121] Four and five monolayer (ML) CdSe NPs were loaded into aD AC with silicone liquid as the pressure medium. It was found that as the pressure increased, the PL of the NPs blue-shifted monotonically (ca.…”
Section: Methodsmentioning
confidence: 99%